Improving Reverse Engineering Processes by using Articulated Arm Coordinate Measuring Machine - Mahmood, Dhuha Mohammed; Mahmood, Ahmed Zaidan (Al-Khwarizmi Engineering Journal, 2020)
The invention relates to a coordinate measuring machine (CMM) for determining a measuring position of a probe. The AACMM isdepends on the robotkinematics (forward and reverse) in their measurementprinciple, i.e., using the AACMM links and joint angles todetermine the exact workspace or part coordinates. Hence, themeasurements are obtained using an AACMM will be extremely accurate and precise since that ismerely dependent on rigid structural parameters and the only source of measurement error is due to human operators. In this paper, a new AACMM design was proposed. The new AACMM design addresses common issues such as solving the complex kinematics, overcoming the workspace limitation, avoiding singularity, and eliminating the effects of design error by designing a new and compatible AACMM that will incorporate all affective design factors into consideration. Different types of design factors and limitations, which significantly affect the AACMM production fabrication processes, and ultimately.accuracy are given. Cost and time factors effects on the design and manufacturing are found to be the most significant. Two primary manufacturing techniques were used, both of which relied on rigors CAD/CAM iterations resulting in an entirely usable G-Code.Those methods are CNC and 3D printing, the most widely used methods in any industry. Nevertheless, accuracy and ergonomics factors must be considered for precise measurements. The design was validated through various methods, such as the use of finite element measurement techniques, to make sure that the design was structurally correct